Evidências de uma interação direta entre os receptores Mas e AT2 - Daniel Campos Villela (2013)
The angiotensin AT2-receptor (AT2R) and the MAS-receptor for angiotensin 1- 7 [Ang-(1-7)] both belong to the protective arm of the Renin Angiotensin System (RAS). They behave in a very similar way in terms of their physiological (tissue-protective) actions. Studies show some functional MAS/AT2 interactions, but a specific study focusing this interaction has not yet been done. In this study we show a molecular and functional interaction between these two receptors. The molecular interaction between MAS and AT2R was assessed by fluorescence resonance energy transfer (FRET) performed in live HEK-293 cells using expression vectors encoding Mas or AT2R fused in the C-terminus with CFP or YFP. FRET efficiencies were determined by monitoring the increase in the CFP (FRET-donor) fluorescence emission during selective YFP (FRET-acceptor) photobleaching. Functional interactions of AT2R and Mas were assessed compering the effects produced by concomitant excitation of both receptors with the well-known effects produced by activation of the Mas receptor alone. In this way, we evaluated the effects of a Mas/AT2 concomitant activation in baroreflex sensitivity in spontaneously hypertensive rats (SHR), in wistar rats aortic ring preparation and in NO release from transfected chinese hamster ovary cell (CHO). Finally, we developed and evaluated the endothelial function of Mas/AT2 double knockout mice with two different backgrounds, C57BL/6 (B6) and FVB/N. Our results show a significant FRET efficiency of 10.8±0.8% when AT2-YFP and MAS-CFP were co-expressed indicating heterodimerisation. Both, MAS and AT2R also formed homodimers as demonstrated by FRET efficiencies of 7.4±0.8% or 9.2±0.8%, respectively. Receptor interactions were specific as no FRET efficiency was observed with an unrelated transmembrane receptor, and expression of non-fluorescent MAS and AT2R competed with FRET efficiencies. Further more, a mutation in the Cys35 of the AT2 receptor reduced significantly the FRET efficiency suggesting that a disulfide bond in this site may be responsible for the heterodimerization between the receptors. Intra-cerebral ventricular (ICV) infusion of Ang-(1-7) or the AT2 R agonist, Compound 21 (C21), baroreflex sensitivity (1.0 ± 0,13 beats/min/mmHg) and (0.93 ± 0,12 beats/min/mmHg) when compared with there controls (0.60 ± 0,09 beats/min/mmHg) (0,60 ± 0,08 beats/min/mmHg; p<0.05) respectively. Interestingly, there was no significant change in barorreflex sensitivity when C21 was infused concomitantly with Ang-(1-7) (before, 0.56 ± 0,04 and 3h after ICV infusion 0,52 ± 0,1 beats/min/mmHg). In the aortic ring assay, the vasorelaxant effect of Ang-(1-7) was blocked after a C21 (10-6 M) administration, 10 minutes before Ang-(1-7). Interestingly, in CHO cells that stably express the Mas receptor, the Ang-(1-7)-MasR mediated NO release was not affected by pre-incubation, 10 minutes before, with C21. Suggesting that the inhibition of C21 observed in the aortic ring assay, is AT2 mediated, once CHO cells do not express the AT2 receptor. The Mas/AT2 double knockout (DKO) mice in the background FVB/N have endothelial and vascular dysfunction. The main evidence provided in this study, is that Mas and AT2 receptors form heterodimers and that this heterodimerization has functional relevance that was observed in several invivo and invitro assays.